India’s Policy Trilemma in an AI‑Driven World: Protectionist Tariffs, WTO Law, and Securing Supply Chains - Deepansh Jain; Gayathry S Nair (Academic Bright Collaboration, 2026)
This paper examines India’s use of protectionist tariffs on information and communication technology (ICT) products in light of its commitments under the multilateral trading system and its objective of integrating into artificial intelligence (AI)–enabled global value chains. The study adopts a qualitative, doctrinal, and analytical approach. It analyses India’s domestic tariff framework, relevant WTO disciplines including GATT Article II and the Information Technology Agreement, and draws on comparative and secondary literature on AI-driven supply chains and industrial policy. The analysis suggests that sustained tariff escalation on ICT inputs raises production costs, slows the adoption of AI technologies, and generates legal tensions under WTO rules. These effects undermine India’s competitiveness in emerging digital value chains. Comparative evidence indicates that long-term technological advancement is more effectively achieved through capability building, innovation policy, and state–industry coordination rather than persistent tariff protection. The study is interpretive and does not employ empirical or econometric methods. Its conclusions are based on doctrinal analysis and secondary sources, and therefore do not quantify the magnitude of economic effects. The paper contributes by integrating trade law, industrial policy, and AI-driven supply-chain analysis within a single framework. It offers a novel interpretation of India’s policy trilemma by linking WTO constraints with the technological requirements of digital production systems.